'Gateway': An Innovative Pedagogical Approach to Prepare Social Care Workers for Social Work Training. Issue 1 (1st January 2023) - Leonard, Kate; Mason, Karl; Pearce, Jill; Jackson, Cleve
Abstract : This article presents a case study of an innovative course requested, funded and designed by the West London Social Work Teaching Partnership (WLSWTP). Due to difficulties in recruiting social workers across these local authorities, the graduate certificate in social care recognised and developed the skills of the current local social care workforce, many of whom were already undertaking roles previously undertaken only by social workers. Many social care workers were unable to access social work qualification routes because they were not in a position to study independently or did not have the required qualifications for bursaried programmes at universities or through fast-track providers. The delivery of a graduate certificate in social care, over one academic year, one day a week, offered the opportunity for social care workers across adult's and children's services to provide evidence of their ability to study at degree level. Those students completing at a 2:1 level met the academic entry requirements for the MSc course at one of the partner universities and one fast track route. The case study outlines the course development, curriculum design and preliminary findings from an ongoing evaluation.